Hubungan Daya Ledak Otot Tungkai Dengan Kecepatan Tendangan Lurus Pencak Silat Siswa SMP Negeri 1 Halmahera Selatan - Djoronga, Rahayu; Saiman, Rifaid (Peneliti.net, 2025)
This study aims to determine the relationship between leg muscle explosive power and straight kick speed of pencak silat students at SMP Negeri 1 South Halmahera. This study is a correlational research design. The subjects of the study were students of SMP Negeri 1 South Halmahera. The data sources came from tests and measurements. The results of the study showed that leg muscle explosive power with straight kick speed obtained an r-count value of 0.984 and a sig. value of 0.000. Because the r-count value = 0.984 and the sig. value = 0.000 <α = 0.05, then there is a relationship between leg muscle explosive power and straight kick speed of pencak silat students at SMP Negeri 1 South Halmahera. The conclusion of this study is that there is a relationship between leg muscle explosive power and straight kick speed of pencak silat students at SMP Negeri 1 South Halmahera.